A Comparative Analysis Of COVID-19 Mortality Rate Across the Globe: An Extensive Analysis of the Associated Factors - Vineet Jain; Nusrat Nabi; Kailash Chandra; Sana Irshad; Varun Kashyap; Sunil Kohli; Arun Gupta (Masters Program in Public Health, 2021)
Background: The vast variation in COVID 19 mortality across the globe draws attention to potential risk factors other than the patient characteristics that determine COVID-19 mortality, this study aimed to analyze and apply evidence-based explanation for the impact offactors associated with COVID-19-related mortality.Subjects dan Method: This was a cross sectional study of global database for wide set of factors associated with COVID-19 mortality, ranging from disease related co-morbidities, socioeconomic factors, healthcare capacity and government policy and interventions. Data for population, total cases, total COVID mortality, tests done, and GDP per capita were extracted from the worldo